Inherited deficiency of the third component of human complement (C′3) - Alper, Chester A. (1969)
A kindred has been investigated in which seven individuals were found to have half-normal serum concentrations of the third component of complement (C′3). This partial deficiency was transmitted as an autosomal dominant trait. Affected individuals were entirely healthy. Hemolytic complement titers were slightly reduced but immune adherence titers and reagent titrations of the classical complement components were normal. Examination for C′3 allotypes revealed that all affected individuals had patterns resembling those of homozygotes. Analysis of the inheritance of C′3 structural genes disclosed that the most likely mechanism for partial C′3 deficiency in this family was nonexpression of one allele.